1995
DOI: 10.1105/tpc.7.11.1859
|View full text |Cite
|
Sign up to set email alerts
|

The petunia MADS box gene FBP11 determines ovule identity.

Abstract: In contrast to the wealth of information relating to genes regulating floral meristem and floral organ identity, only limited data are available concerning genes that are involved in determining and regulating the identity and development of an ovule. We have recently isolated the floral binding protein 11 (FBP11) MADS box gene from petunia and found that it is expressed exclusively in ovule primordia and subsequently in the ovules, suggesting a role for this gene in ovule formation. To test this hypothesis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
203
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(207 citation statements)
references
References 30 publications
3
203
0
Order By: Relevance
“…In A. thaliana, A function is involved in the specification of sepals and petals, B function in petal and stamen specification, C function in stamen and carpel specification, and E function participates in the specification of all floral organs (Coen and Meyerowitz, 1991;Colombo et al, 1995;Pelaz et al, 2000;Ditta et al, 2004). These functions are all encoded by members of separate MADS-box gene lineages, each of which shows evidence of multiple duplication events (Theissen, 2001).…”
Section: Gene Duplications and Diversification In Mads-box Floral Orgmentioning
confidence: 99%
“…In A. thaliana, A function is involved in the specification of sepals and petals, B function in petal and stamen specification, C function in stamen and carpel specification, and E function participates in the specification of all floral organs (Coen and Meyerowitz, 1991;Colombo et al, 1995;Pelaz et al, 2000;Ditta et al, 2004). These functions are all encoded by members of separate MADS-box gene lineages, each of which shows evidence of multiple duplication events (Theissen, 2001).…”
Section: Gene Duplications and Diversification In Mads-box Floral Orgmentioning
confidence: 99%
“…These carpel-specific genes may well be functionally related to FBP7 and FBPll from petunia, for which mutant phenotypes obtained by cosuppression revealed a function in proper ovule development (Angenent et al 1995b). Recently, transgenic petunia plants ectopically expressing FBPll demonstrated that this gene determines ovule identity (Colombo et al 1995).…”
Section: Agamous-like Mads-box Genesmentioning
confidence: 99%
“…The initiation of ovule primordium formation is caused by expression of class D MADS-box genes such as Arabidopsis SEEDSTICK (STK) and petunia floral binding protein 7 (FBP7) and FBP11 (Angenent et al 1995;Colombo et al 1995;Favaro et al 2003). ARABIDOPSIS BSISTER (ABS) from Arabidopsis and FBP24 from petunia are members of the B sister subfamily, which are necessary to determine the identity of the endothelial layer within the inner integument of the ovule (Nesi et al 2002;de Folter et al 2006).…”
Section: Introductionmentioning
confidence: 99%